Pizzeria by-product: A complementary feed source for Nile tilapia (Oreochromis niloticus) raised in biofloc technology? - de Sousa A.A.* (2019)
© 2018 Elsevier B.V.In face of all problems regarding to the traditional tilapia food sources and production systems the search for sustainable alternatives have been increasing. Within this context, the aim of this study was to evaluate different inclusion levels of pizzeria by-product meal (0, 20, 40, 60, 80 and 100%) in diets for Nile tilapia (Oreochromis niloticus) reared in biofloc systems. Diets were prepared from a pre-existing commercial diet, milled and re-pelleted, containing different inclusion levels (considering 0% as the control group). A total of 288 tilapia juveniles were randomly stocked (2.90 ± 0.02 g) in 24,100-L experimental units (6 dietary treatments with 4 replicates). Water quality parameters and the planktonic community profile were monitored throughout the feeding trial (38 days). Zootechnical performance of fish fed the 20% pizzeria by-product feed was statistically equal (p > 0.05) to those fed the control feed. Feed conversion ratio was also similar (p > 0.05) between these treatments, as well as with the 40% inclusion group. During the experimental period, seven taxa of planktonic organisms were characterized in the bioflocs. According to economic analysis and performance data, it is possible to successfully include up to 20% of pizzeria by-product meal in diets for Nile tilapia reared in biofloc systems, and 40% inclusion of pizzeria by-product might exhibit a strategic economic benefit to the farms that also commercialize fingerlings.